Targeting leukemic stem cell subpopulation in AML using phytochemicals: An in-silico and in-vitro approach. (March 2023) - Brahmbhatt, Jpan; Kumar, Sivakumar Prasanth; Bhadresha, Kinjal; Patel, Maulikkumar; Rawal, Rakesh
Abstract: It has been indicated that leukemic stem cells (LSCs), a subset of leukaemia cells, are responsible for therapy resistance and relapse in acute myeloid leukaemia (AML). Therefore, the current study aimed to discover an LSC biomarker in AML patients and identify a natural compound that may target the same. By performing the different gene expression analyses, we identified 12 up-regulated and 192 down-regulated genes in LSCs of AML compared to normal bone marrow-derived HSCs. Further STRING interaction, GO enrichment and KEGG pathway analysis were carried out to top hub genes. Wilms' tumour-1 (WT1) transcription factor was pointed out as the top hub gene and a potential biomarker for LSCs in AML. For the targeted inhibition of WT1, we performed screening and stimulation of potential natural compounds. The results revealed Gallic acid (GA) and Chlorogenic acid (CA) as promising WT1 inhibitors. In-vitro validation of cytotoxic effects of both GA and CA on THP-1 and HL-60 cell lines suggested that both these compounds inhibited cell proliferation. Still, GA has a more cytotoxic effect compared to CA. Next, we performed cell cycle analysis and apoptosis analysis and found that both compounds arrested cells in G0/G1 phase and induced apoptosis in both cell lines. Surprisingly, a significant decrease in colony formation and cell migration was also observed. However, GA gave more promising results in all cellular assays than CA. Furthermore, we studied the mRNA expression of WT1 and BCL2, which are transcriptionally activated by it. We found that GA significantly downregulated both these genes compared to CA. Our results suggested that GA is a potential inhibitor of WT1 and might be an excellent anti-LSCs natural drug for AML patients. Highlights: Identification of differentially expressed genes in LSCs of AML. Primary strategy to develop effective therapy for AML using natural medicine. WT1 MD stimulation to identify natural drug target. Gallic acid could be a natural anti-LSCs drug for AML patients with high WT1 expression.